(untitled) (PerCursos, 2025)
This article investigates the use of remote sensing in textbooks for the New High School, focusing on the collections approved by the National Program of Textbooks and Teaching Materials (PNLD) for the area of Human and Social Applied Sciences (CHSA). The main objective was to analyze how this theme is addressed and how it contributes to a critical understanding of geographic space, promoting interdisciplinarity. The bibliographic and documentary research analyzed 14 collections (84 books), using quantitative criteria (number of mentions) and qualitative criteria (interdisciplinary, theoretical, and methodological approach to remote sensing and basic cartography). The collections were classified into three categories: not recommended, partially recommended, and recommended, based on alignment with the National Common Curricular Base (BNCC). The results showed that, although satellite images are present in all collections, remote sensing as a specific theme is poorly explored, appearing in only 47.62% of the works. The analysis revealed a lack of in-depth theoretical grounding and a superficial use of satellite images, with limited development of their interdisciplinary potential. A deficiency in content related to basic cartography was also observed. It is concluded that the approach to remote sensing in the analyzed textbooks is limited, requiring teachers to seek complementary resources to promote a more effective learning of geotechnologies in high school.